Synthesis of Sulfonimidamide‐Based Amino Acid Building Blocks with Orthogonal Protecting Groups. Issue 5 (2nd January 2019) - Chinthakindi, Praveen K.; Benediktsdottir, Andrea; Ibrahim, Ayah; Wared, Atta; Aurell, Carl‐Johan; Pettersen, Anna; Zamaratski, Edouard; Arvidsson, Per I.; Chen, Yantao; Sandström, Anja
Abstract : Herein, we report the synthesis of novel sulfonimidamides (SIAs) based on amino acid building blocks using a one‐pot method from tert ‐butyldiphenylsilyl‐protected (TBDPS) sulfonamides, as well as exploration of orthogonal deprotection strategies. Among the several protecting groups investigated, TBDPS showed higher conversion, allowed UV detection and simple diastereomeric separation; in particular in combination with amino acid tert‐ butyl esters. Moreover, we applied the present method to synthesize cyclic five‐membered acyl sulfonimidamides in two steps. The described synthesis of SIA‐based amino acid building blocks in combination with the orthogonal protection groups provide access to unnatural amino acid building blocks useful for further incorporation into larger molecules, such as peptide‐based transition‐state analogues and peptidomimetics. The chirality of the SIA group, as well as its additional point of diversity provided by the extra NH group, creates opportunities for the development of unique compound libraries that explore new chemical space, which is of considerable importance for the pharmaceutical and agrochemical industry. Abstract : Sulfonimidamide‐based amino acid building blocks have been synthesized through one‐pot reductive chlorination from sulfonamides followed by nucleophilic substitution with amino acid esters under mild conditions. Suitable orthogonal protecting groups were investigated that also allowed easy separation of diastereomers and access to non‐chromophoric sulfonimidamides as well as cyclic acyl sulfonimidamides.